Budget Impact Analysis of Mepolizumab for Eligible Patients in the Setting of a Severe Asthma Clinic Within Dubai Health Authority (DHA) - Mahboub B; Mohy A; El-Amir I; Lukić T; Gouhar R; Noibi S (Dove Medical Press, 2022)
Bassam Mahboub,1 Ahmed Mohy,2 Islam El-Amir,2 Tamara Lukić,3 Raef Gouhar,4 Saeed Noibi5 1Pulmonary Medicine Department, Rashid Hospital, Dubai Health Authority, Dubai, United Arab Emirates; 2Medical Affairs Department, GSK, Jeddah, Kingdom of Saudi Arabia; 3GSK Research and Development, Dubai, United Arab Emirates; 4Medical Affairs Department, GSK, Dubai, United Arab Emirates; 5Medical Excellence and Value Access, Emerging Markets Region, GSK, Jeddah, Kingdom of Saudi ArabiaCorrespondence: Raef Gouhar, Medical Affairs Department, GSK, Dubai, United Arab Emirates, Email raef.a.gouhar@gsk.comPurpose: To estimate 5-years budgetary impact of introducing mepolizumab to eligible patients with uncontrolled severe eosinophilic asthma treated at a tertiary care hospital within Dubai Health Authority (DHA).Patients and Methods: A budget impact analysis (BIA) model was adapted to the setting of Rashid Hospital, DHA to estimate the budgetary implications of introducing first-in-class anti-IL5 (mepolizumab) as add-on therapy for eligible patients with severe eosinophilic asthma. The eligible patient population (n=60) was estimated from aggregate data provided by the clinic. Patients were eligible to treatment with mepolizumab if they had ≥ 2 exacerbation in the previous year and eosinophil count ≥ 150 cell/μL. The analysis compared the cost of treating patients in two alternative scenarios; a scenario where patients are treated with optimized usual care or with available biologic as add-on therapy, and a second scenario where mepolizumab is fully accessible to eligible patients.Results: Administration of mepolizumab to eligible patients at Rashid Hospital is predicted to result in overall savings estimated at £ 270,545 over a 5-year time horizon. Exacerbation rates could not be indirectly compared for mepolizumab and omalizumab, since treatment continuation rules were defined differently. Therefore, these parameters were directly taken from the clinical trials for mepolizumab and omalizumab. The savings were estimated due to drug acquisition costs (£ 269,900) and estimated reduction in exacerbation (n=15). One-way sensitivity analysis showed that the model results was most sensitive to changing the method of calculating omalizumab dose and varying the drug acquisition cost of omalizumab by ± 20%.Conclusion: The BIA showed that full accessibility of mepolizumab to eligible severe asthma patients is predicted to be budget saving in the Dubai Health Authority. This evaluation is relevant to healthcare decision making as it demonstrates that mepolizumab is budget saving for eligible patients, while reducing burden by improving their control and symptoms.Keywords: asthma phenotypes, eosinophil count, exacerbations, anti-IL5, treatment cost